Accuracy on trauma cervical spine radiograph interpretation among emergency medicine trainees - Abd Kursi, Abdul Latif (2008)
Emergency Physician face a great challenge in the diagnosis of cervical spine injuries, therefore radioimaging is use as an important aid for diagnostic purposes. Emergency Physician must be prepared to manage patient with potential injuries to cervical spine efficiently and effectively and act accordingly. Standard cervical film trauma series is routinely performed in Emergency Department after primary assessment has been made. Lateral and anterior-posterior view is performed in trauma case with suspected cervical spine injury. This study is performed to determine the accuracy of cervical spine radiograph interpretation among the emergency medicine trainees in Hospital Universiti Sains Malaysia.